Prognostic factors and treatment outcomes in pediatric autoimmune encephalitis: a multicenter study - Abu Melha, Ahlam Ahmed; Aldress, Amjad Saad; Alamri, Fahad; Aljomah, Lama Saleh; Hommady, Raid; Al-Rumayyan, Ahmed; Albassam, Fahad (Frontiers in Neurology, 2024)
Introduction The last few decades have increased our understanding of autoimmune encephalitis (AE). In both the pediatric and adult populations, it proves to be a disease of dramatic acute onset of heterogeneous clinical manifestations, notably encephalopathy with neuropsychiatric symptoms, seizures, and extrapyramidal symptoms. More often, it is triggered by a viral infection in the pediatric age groups, as suggested by the preceding febrile symptoms in over half of cases, and more ostensibly, NMDAR encephalitis post herpes encephalitis. An underlying neoplasm may be present in certain types (i.e., NMDAR encephalitis). The rising rate of antibody detection and subsequent confirmation has been boosted by improved live cellular assay detection methods. The corresponding clinical phenotypes, common underlying malignancies, and histopathological findings have helped improve our management regarding intervention and choice of immunotherapy. New assessment tools such as the Clinical Assessment Scale in Autoimmune Encephalitis (CASE score) have helped improve the objective assessment of impact on cognitive functions (1). Early intervention with immunotherapy (and tumor removal in proven underlying neoplasms) has improved overall outcomes in most presenting patients. But nearly 40% of cases fail to respond to the first tier of treatment (2). The complex interplay between pathogenic autoantibodies, T-cells, B-cells, and cytokines has led to the emergence of additional immunotherapy agents (i.e., tocilizumab and bortezomib). Methods In this retrospective observational study of pediatric AE conducted at two tertiary care centers, we observed the clinical characteristics, autoantibody yield, treatment modalities used, and disability scores during presentation and follow-up. Our secondary aim was to delineate prognostic factors for poor outcomes. Results Neuropsychiatric symptoms, encephalopathy, and seizures were the predominant manifestations in most of our patients. Younger age groups, refractory seizures, profound encephalopathy, and refractory disease harbored higher disability scores. The group that received combined immunotherapy has shown mitigation of disability score from severe to mild during long-term follow-up, signifying the role of multifaceted immunotherapy in pediatric refractory AE. Conclusion Early implementation of combined immunotherapy in refractory cases significantly improved longterm disability scores, in spite of lingering residual effects on neurologic functions, notably cognition, behavior, and speech.